Violence and the state in Languedoc, 1250-1400 - Firnhaber-Baker, Justine (Cambridge studies in medieval life and thought, 2014)
Although it is often assumed that resurgent royal government eliminated so-called 'private warfare', the French judicial archives reveal nearly one hundred such wars waged in Languedoc and the Auvergne between the mid-thirteenth and the end of the fourteenth century. Royal administrators often intervened in these wars, but not always in order to suppress 'private violence' in favour of 'public justice'. They frequently recognised elites' own power and legitimate prerogatives, and elites were often fully complicit with royal intervention. Much of the engagement between royal officers and local elites came through informal processes of negotiation and settlement, rather than through the imposition of official justice. The expansion of royal authority was due as much to local cooperation as to conflict, a fact that ensured its survival during the fourteenth-century crises. This book thus provides a new narrative of the rise of the French state and a fresh perspective on aristocratic violence